2006
DOI: 10.1097/01.pec.0000195764.50565.8c
|View full text |Cite
|
Sign up to set email alerts
|

Signs and Symptoms of Cerebrospinal Fluid Shunt Malfunction in the Pediatric Emergency Department

Abstract: In this study, lethargy and shunt site swelling were predictive of shunt malfunction. Other signs and symptoms studied did not reach statistical significance; however, one must maintain a high index of suspicion when evaluating children with an intracranial shunt because the presentation of malfunction is widely varied. A missed diagnosis can result in permanent neurological sequelae or even death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…Se estima que entre 25 y 46% de las derivaciones tienen un mal funcionamiento durante el primer año después de haber sido instaladas 4,5 , siendo la obstrucción mecánica y las infecciones, las dos principales causas de disfunción valvular 6,7 . La tasa de infección post instalación de DVP en la población infantil se estima en 10% y fl uctúa entre 0 y 22% [8][9][10][11] , siendo una causa importante de morbimortalidad 12 .…”
Section: Correspondencia Aunclassified
“…Se estima que entre 25 y 46% de las derivaciones tienen un mal funcionamiento durante el primer año después de haber sido instaladas 4,5 , siendo la obstrucción mecánica y las infecciones, las dos principales causas de disfunción valvular 6,7 . La tasa de infección post instalación de DVP en la población infantil se estima en 10% y fl uctúa entre 0 y 22% [8][9][10][11] , siendo una causa importante de morbimortalidad 12 .…”
Section: Correspondencia Aunclassified
“…3,8,9 To a certain degree, the content of the protocol was arbitrary. Its purpose was to facilitate the physician decision-making process by obtaining imaging studies in a timely fashion.…”
Section: Clinical Pathway Protocolmentioning
confidence: 99%
“…One study estimated that an episode of ventricular shunt failure will occur in 85% of patients within 15 years of device insertion 3 with 30%-40% of ventricular shunts failing after the first year of insertion. 4 Kim et al 5 reported a ventricular shunt mortality rate of 2.2%. The clinical diagnosis of shunt malfunction is further complicated by nonspecific clinical signs, which can be attributed to other common pediatric ailments.…”
mentioning
confidence: 99%
“…The clinical diagnosis of shunt malfunction is further complicated by nonspecific clinical signs, which can be attributed to other common pediatric ailments. 5,6 CT evaluation of ventricular size, in conjunction with clinical symptoms, is the primary means of assessing ventricular CSF shunt failure/malfunction in pediatric patients with closed fontanelles. 5 However, concerns were expressed regarding the use of CT in children, 7 primarily because they are more sensitive than adults for some cancers, one of which is radiation-induced brain tumor.…”
mentioning
confidence: 99%